Takotsubo cardiomyopathy associated with sepsis due to Pseudomonas aeruginosa pneumonia doi: 10.12662/2317-3076jhbs.v3i4.169.p242-244.2015 - Pereira, Márcio da Silva; Sarubbi, Gabriel Dantas; Rodrigues, Renan Barbosa; Fontenele, Maria Rafaelle Lourenço; Queiroz Lemos, Daniele Rocha (Journal of Health & Biological Sciences, 2015)
The authors describe a case report of a 71 year-old female patient admitted at the emergency service due to severe precordial chest pain associated with dyspnea and sweating. The electrocardiogram performed on admission showed ST elevation on V2 and V3 leads and the ventriculography revealed left ventricular apical ballooning, denoting the diagnosis of Takotsubo Cardiomyopathy. At the eighth day of hospitalization, although the heart function was recovered, the patient died due the clinical complications of a septic shock.